Participatory Communication and Affecting Factors on Empowering Women Farmers in The Urban Farming Program at Bogor City and Bogor Regency - Selly Oktarina; Sumardjo Sumardjo; Ninuk Purnaningsih; Dwi Retno Hapsari (Nyimak: Journal of Communication, 2022)
Urban farming is essential as an effort to overcome land limitations and weak productivity in the food supply. Urban farming from a communication perspective is an empowerment effort that directly involves the community in its implementation. This study aims to analyze the participatory communication of women farmers and analyze factors that affect the application. This study was conducted in Bogor City and Bogor Regency. This study is explanatory survey research with a quantitative approach and supported by qualitative data. The data obtained is by cluster sampling with urban, semi-urban, and rural clusters on 231 respondents. Data were analyzed using the score, Difference Test, and Structural Equation Model (SEM). The results show that the participatory communication level in the urban farming program is medium, referring to the dialogue atmosphere, dialogue participation, and convergence level. The factors that significantly influence participatory communication are characteristics, champion competence, the exposure of media communication, and institutional support.Keywords: Communication, dialogue, participation, urban farming ABSTRAKUrban farming penting sebagai upaya mengatasi keterbatasan lahan dan lemahnya produktivitas dalam penyediaan pangan. Urban farming dari perspektif Komunikasi merupakan upaya pemberdayaan yang melibatkan secara langsung masyarakat dalam pelaksanaannya. Fokus penelitian ini adalah menganalisis komunikasi partisipatif wanita tani dan menganalisis faktor-faktor yang berpengaruh terhadap komunikasi partisipatif dalam pelaksanaan program urban farming. Penelitian dilakukan di Kota Bogor dan Kabupaten Bogor. Penelitian ini bersifat survey explanatory research dengan pendekatan kuantitatif dan didukung data kualitatif. Pengambilan sampel secara cluster sampling dengan klaster kelurahan yang dikelompokkan berdasarkan urban, semi urban dan rural terhadap 231 orang wanita tani. Analisa data dilakukan dengan metode skor, uji beda serta analisis structural model (SEM). Hasil penelitian menunjukkan bahwa komunikasi partisipatif wanita tani dalam program urban farming berada pada kriteria sedang yang dilihat dari suasana dialog, partisipasi dialog dan tingkat konvergensi. Faktor yang berpengaruh signifikan terhadap komunikasi partisipatif adalah pendidikan formal, luas lahan, kompetensi pemberdaya, terpaan media komunikasi, dan dukungan lembaga.Kata Kunci: Dialog, komunikasi, partisipasi, urban farming